Womens Awareness In Bandung City Toward Gender Equality During the Covid-19 Pandemic - Mohammad Apridio Salahuddin Hakim; Elizabeth Darien Irawan; Muhammad Hafid Fadhilah Dipradja; Zalfa Nurhanna Rachmah; Nuraeni Nuraeni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The COVID-19 pandemic has had a significant impact on the people of Indonesia, especially in Bandung, which is marked by an increase in the number of layoffs and unemployment. Unemployment dominated by working-age people is a threat to gender equality due to uncertain economic conditions that have a worse impact on women than men. This phenomenon also has an impact on increasing violence against women and divorce in Bandung City in the era of the COVID-19 pandemic, showing that women's awareness of the values of gender equality, women's empowerment, and sustainable development goals have not been realized. This article uses descriptive quantitative research methods supported by SPSS software. The data sources we need to obtain include secondary and primary data. In the analysis that has been done, the data shows that women have shown empowerment, which can be seen from their involvement in activities carried out by women in the city of Bandung. The active role of the government and related institutions is still needed to strengthen awareness of gender equality issues by all parties as a very important factor in achieving equitable and sustainable development.